Konflik Kedaulatan Laut Natuna Indonesia dengan China Selatan dalam Perspektif Hukum dan Pendekatan Kemiliteran di Indonesia - Saskia Nursukma Andriliani; Irwan Triadi (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
State sovereignty is a prerogative right that must be maintained as a priority, especially in Indonesia is archipelagic geography. This presents a significant challenge in maintaining sovereignty over the Natuna Islands and Lingga Islands in Riau Islands Province, Indonesia. This area has been the subject of international conflict, particularly concerning China's claim under the Nine-Dash Line, which the Chinese government justifies with historical arguments and past governmental decisions. However, this claim lacks a valid legal basis under international law, including the United Nations Convention on the Law of the Sea (UNCLOS) 1982, which defines international maritime boundaries. The conflict began to escalate in 2016 following the arrest of three Chinese fishermen involved in large-scale illegal fishing, an act supported by the Chinese government. In response, the Indonesian government took measures to assert its sovereignty by strengthening military security, engaging in diplomatic efforts with ASEAN member states, and conducting best practice studies to potentially bring the Natuna Sea sovereignty dispute before the International Court of Justice. Indonesia's sovereignty over the Natuna Sea is firmly supported by the Djuanda Declaration and the 1982 UNCLOS Agreement. This study aims to analyze the Natuna conflict using a Normative Law and Military approach as the primary strategies to resolve disputes over the Natuna Sea.